2016
DOI: 10.1111/ans.13666
|View full text |Cite
|
Sign up to set email alerts
|

Results of colon cancer surgery in patients over 75 years old

Abstract: Age does not influence the surgical results after colon cancer resection but is associated with increased postoperative morbidity and mortality. CSS is lower in patients who are ≥75 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…We focused our analysis on patients with rectal cancer because they accounted for over 80% of those receiving radiation therapy. Consistent with these results, Pérez Domínguez L et al found that age did not affect the prognosis after colon cancer resection but was associated with more postoperative morbidity and mortality [ 22 ].…”
Section: Discussionsupporting
confidence: 55%
“…We focused our analysis on patients with rectal cancer because they accounted for over 80% of those receiving radiation therapy. Consistent with these results, Pérez Domínguez L et al found that age did not affect the prognosis after colon cancer resection but was associated with more postoperative morbidity and mortality [ 22 ].…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies mainly focused on perioperative clinical outcomes of elderly patients with colorectal cancer. 11,12 However, as relatively more studies were conducted on octogenarian or younger patients, few studies focused exclusively on nonagenarian patients who underwent colorectal surgery. [13][14][15][16][17][18][19] The postoperative short-and long-term complication rates in this study were 35.0% and 15.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery remains the mainstream treatment for elderly CRC. Some studies have reported that elderly patients undergoing open colorectal surgery are associated with high mortality (2.1–7.9%) and morbidity (17.7–50.0%) when compared with younger people [ 4 , 5 , 6 ]. Advanced age is associated with increasing comorbidities, such as diabetes mellitus, chronic kidney disease, and cardiovascular or pulmonary disease, which increase surgical morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%